Mid‐Infrared Pyroresistive Graphene Detector on LiNbO3. Issue 4 (27th December 2016) - Gopalan, Kavitha K.; Janner, Davide; Nanot, Sebastien; Parret, Romain; Lundeberg, Mark B.; Koppens, Frank H. L.; Pruneri, Valerio
Abstract : Graphene on a z‐cut LiNbO3 pyroresistive platform allowing infrared light detection is shown. Light is absorbed by the LiNbO3 crystal substrate. The subsequent temperature increase, via the pyroelectric effect, induces polarization (bound) charges at the crystal surface. These cause doping into graphene which in turn changes its carrier density and conductivity.